2x+1+5x*2x-1=36

Simple and best practice solution for 2x+1+5x*2x-1=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+1+5x*2x-1=36 equation:



2x+1+5x*2x-1=36
We move all terms to the left:
2x+1+5x*2x-1-(36)=0
We add all the numbers together, and all the variables
2x+5x*2x-36=0
Wy multiply elements
10x^2+2x-36=0
a = 10; b = 2; c = -36;
Δ = b2-4ac
Δ = 22-4·10·(-36)
Δ = 1444
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1444}=38$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-38}{2*10}=\frac{-40}{20} =-2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+38}{2*10}=\frac{36}{20} =1+4/5 $

See similar equations:

| 5y+y=5y-2 | | 8x^+6x=5 | | 2x^2+62=0 | | 1/x+1/12-x=3/8 | | F(20)=4x+12 | | -9=3+t | | 9r+15=-12 | | 37.5+x=50 | | 7×=4x+27 | | u+3.9=9.85 | | x+12=–15 | | 2d=2,4 | | a+12.5=10.1 | | 2y+10y+3y=y | | 35.3=d-(-3.81) | | y-1.7=2.89 | | 8x9=x | | 3/4q=1/3 | | 3x+2−4x+1+9x=6x−1 | | —14+3(x+10)=7(2x+4)+x | | 60x=-9216+688 | | 3(x+87)=75 | | (9x^2-7x+5)-(12x^2-5x-6)= | | -148=64q | | 10v−5v=15 | | -144=64q | | x-4/5=1/5 | | y=75(2) | | x+8/5=1/5 | | 5x-7=14x | | 2^n=6000 | | 8x+797=837 |

Equations solver categories